Skills and Strategies Required for Visual Teaching Literacy in Preschool Education - Andrea Soto-Grant (Universidad Nacional, Costa Rica, 2018)
This article refers to the results of data collection and the theoretical research conducted as part of a research project to obtain a master’s degree; the research aimed to develop methodologies and materials for stimulation of visual literacy with children in preschool. The following sections theorize the context in which the theme of image reading is developed. The conceptualization of the terms relating to visual literacy to establish parameters for the collection and analysis of data is also set. A quantitative approach with a descriptive methodology was used to collect the data. The data for this research were collected through interviews with teachers selected from a preschool educational level; it was a convenience sampling to which a self-administered questionnaire with several types of dichotomous, multiple-choice, open and closed questions was applied. Among the results obtained, a lack of knowledge on the concept and importance of visual literacy was revealed, as well as how to implement this literacy in their preschool classrooms. The lack of specific teaching strategies for the stimulation of this type of literacy with children is also highlighted.